Derivation and characterization of an embryonic‑derived muscle progenitor cell line from Atlantic salmon (Salmo salar) - Kyle Naylor; Sophia Webb; Deepika Rajesh; Patrick J. Mee (In Vitro Cellular & Developmental Biology - Animal, 2026)
Unlike mammals, teleost fish exhibit lifelong skeletal muscle growth, characterized by continued fiber hypertrophy and the formation of new muscle fibers maintained by a persistent progenitor cell population. However, the limited availability of stable muscle progenitor cell lines from commercially important species such as Atlantic salmon ( Salmo salar ) constrains mechanistic studies and emerging applications in cellular aquaculture. Here, we report the establishment and characterization of a novel embryonic-derived salmon muscle progenitor cell line, termed SsEC. These cells were derived from late embryonic stages and exhibited a spindle-shaped morphology, robust proliferative capacity, and sustained expansion beyond 30 passages under defined culture conditions. SsECs demonstrated a distinct extracellular matrix preference, with vitronectin supporting long-term maintenance and expansion. Molecular characterization confirmed stable expression of canonical myogenic markers, including myf5 and myod1 , while transcriptomic profiling revealed enrichment of genes associated with muscle development and sarcomere organization relative to a non-myogenic salmon cell line. Directed differentiation to muscle, using a two-step protocol, induced efficient formation of multinucleated myotubes expressing myosin heavy chain and sarcomeric α-actinin, with upregulation of key differentiation markers such as myog and tnnt3a . Together, these findings establish SsECs as a robust in vitro model cell line for studying salmon muscle development and provide a novel platform for applications in aquaculture research and cellular seafood production.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Uncertain times require new thinking for agri-food science to ensure food security and nutrition for all - Evan D.G. Fraser; Olanike Adeyemo; Marie-Josèphe Amiot-Carlin; Sayed Azam-Ali; Patrick Caron; Martin Cole; Jennifer Clapp; Mahmud Duwayri; Ruben Echeverría; Cecilia Elizondo; Hilal Elver; Bernard Lehmann; et al. (Trends in Food Science & Technology, 2025)

Evolving physical and mechanical rock properties during exposure at Earth's surface - Monica Rasmussen; Martha Cary Eppes; Yang Yuan; Philip G. Meredith; Karin Hofer Apostolidis; Thomas Mitchell; Alex J. Rinehart; Amit Mushkin; Patrick Webb; Valerie Reynolds; Alan J. Hidy; Samantha Berberich; et al. (Geomorphology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Multisectoral behavior change intervention improves diet quality, but not food security, in rural Uganda - Regina Brown; Stacy Griswold; Carolyn Van Sant; Ian Moore; Yanlin Ren; Gloria Desire Kayo; Jackson Bagabirwa; Merry Fitzpatrick; Anastasia Marshak; Marlene Hebie; Hugo De Groote; Patrick Webb; et al. (Global Food Security, 2024)

Integrating behavioural, material and environmental science to inform the design and evaluation of a reuse system for takeaway food - Maryam Hoseini; Sarah C. Greenwood; Saima Eman; Paul Mattinson; Harriet M. Baird; Rorie Beswick-Parsons; J. Patrick A. Fairclough; Thomas L. Webb; Anthony J. Ryan; Rachael H. Rothman (Resources, Conservation and Recycling, 2024)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Ensuring societal considerations are met when translating science into policy for sustainable food system transformation - Brajesh K. Singh; Evan D.G. Fraser; Tom Arnold; Patricia Biermayr-Jenzano; Jacqueline E.W. Broerse; Gianluca Brunori; Patrick Caron; Olivier De Schutter; Karen Fabbri; Shenggen Fan; Jessica Fanzo; Magdalena Gajdzinska; et al. (Trends in Food Science & Technology, 2023)

Seaweed's contribution to food security in low- and middle-income countries: Benefits from production, processing and trade - Patrick Webb; Natalie K. Somers; Shakuntala H. Thilsted (Global Food Security, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

The effects of male out-migration on household food security in rural Nepal - Jeeyon Janet Kim; Elizabeth Stites; Patrick Webb; Mark A. Constas; Daniel Maxwell (Food Security, 2019)

Measuring multiple facets of malnutrition simultaneously: the missing link in setting nutrition targets and policymaking - Patrick Webb; Hanqi Luo; Ugo Gentilini (Food Security, 2015)

Ecological Responses to Flow Alteration: Assessing Causal Relationships with Eco Evidence - J. Angus Webb; Susan J. Nichols; Richard H. Norris; Michael J. Stewardson; Stephen R. Wealands; Patrick Lea (Wetlands, 2012)

“He said, she said”: who should speak for households about experiences of food insecurity in Bangladesh? - Jennifer C. Coates; Patrick Webb; Robert F. Houser; Beatrice Lorge Rogers; Parke Wilde (Food Security, 2010)